COMPARATIVE ANALYSIS OF THE LEGAL NATURE OF BLOCKCHAIN AND SMART CONTRACTS: FROM PURE TECHNOLOGY TO LEGAL PERSONALITY - Chmielarz, Patryk (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Today, with the expansion of international trade, the infrastructures associated with this field have also experienced remarkable growth. Among these, two relatively emerging technologies—blockchain and the smart contracts formed on its basis—have emerged with the aim of accelerating, facilitating, and enhancing the security of financial and commercial transactions. Given the increasing pervasiveness of these technologies and their deep, potential impact on various aspects of human life and social relations, it is essential to clarify their legal and regulatory status across different domains. Achieving this goal, above all, requires a precise understanding of the nature of these two technologies. This is because, depending on the nature of each, different legal effects arise, and specific sets of rules come to govern them.On the other hand, it must be said that blockchain technology, for several reasons—including the fact that assets existing on this platform do not belong to the network itself—has not been able to acquire a legal nature and has in practice remained confined to its technical dimension. However, the situation is entirely different when it comes to smart contracts. Unlike blockchain, these contracts possess distinct legal attributes, including "legal personality." The reason for this lies both in their ability to operate independently of the contracting parties and in the existence of explicit legal provisions in this regard. This research attempts to provide a comprehensive analysis of the technical and legal nature of blockchain and smart contracts, while precisely explaining the legal issues surrounding blockchain and the smart contracts based on it.